Psychometric Validation of a Questionnaire to Assess Perception and Knowledge About Exposure to Pesticides in Rural Schoolchildren of Maule, Chile - Muñoz-Quezada, María Teresa; Lucero, Boris; Castillo, Benjamín; Bradman, Asa; Zúñiga, Liliana; Baumert, Brittney O.; Iglesias, Verónica; Muñoz, María Pía; Buralli, Rafael J.; Antini, Carmen (Frontiers in Psychology, 2021)
Exposure to pesticides during infancy is associated with numerous adverse health outcomes. The assessment of knowledge and perception of pesticides exposure and risk among children has not been thoroughly studied. The aim of the study was to evaluate the reliability and validity of a questionnaire that measures the knowledge and perception of exposure to organophosphate pesticides among rural schoolchildren. The questionnaire was administered to 151 schoolchildren between 9 - 13 years from four chilean rural schools. An internal consistency analysis of the ordinal alpha coefficient and a polychoric factor analysis for categorical data were used. The results show that the ordinal alpha was 0.95. Polychoric matrices of rotated components show the 17 questions summarized pesticide knowledge in 5 factors extracted after varimax rotation. This factorial model explains 56.3% of the variance. The questions were grouped as follows: knowledge about pesticides (Factor 1); knowledge of health effects related to pesticides exposure (Factor 2); pesticide exposure through the growing of fruits and vegetables (Factor 3); perception and action against pesticides exposure at school (Factor 4); and perception and action against pesticides exposure at home (Factor 5). The questionnaire provides a useful tool for examining pesticide exposure in agricultural regions, allowing younger community members to participate.